A kind of high wear-resistant brick and preparation method thereof

By using high-purity brown corundum, silicon carbide and mullite and introducing Guangxi white mud as a sintering agent to form a dense composite crystal phase, the problem of poor wear resistance of traditional refractory bricks is solved and the high resistance is significantly improved The wear resistance and peeling resistance of grinding bricks extend the service life.

CN117486623BActive Publication Date: 2025-02-14河南瑞泰耐火材料科技有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311202876.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-18
Publication Date
2025-02-14
Estimated Expiration
2043-09-18

AI Technical Summary

Technical Problem

The traditional cement kiln refractory bricks have poor wear resistance, low bond strength, impermissible erosion, and severe peeling and damage, resulting in a shortened service life and affecting the increase in cement clinker production.

Method used

High-purity brown corundum, silicon carbide and mullite are used as the main raw materials, and Guangxi white mud is introduced as the sintering promoter. By adjusting the particle grading and optimizing the ratio, dense composite crystal phases are formed at high temperatures to improve the resistance of the product. Pressure strength and wear resistance.

Benefits of technology

It significantly improves the wear resistance and peeling resistance of high wear-resistant bricks, extends the service life of masonry bodies, and is suitable for efficient applications in cement kilns.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present application relates to the technical field of refractory materials, and discloses a high wear-resistant brick. The high wear-resistant brick is mainly prepared from the following raw materials in mass percentage: 8-12wt% of brown corundum with a particle size of 5-3mm, 20-25wt% of brown corundum with a particle size of 3-1mm, 18-22wt% of brown corundum with a particle size of 1-0mm; 10-15wt% of mullite with a particle size of 3-1mm, 6-10wt% of mullite with a particle size of ≤0.088mm; 15-20wt% of silicon carbide with a particle size of ≤0.088mm; 6-10wt% of Guangxi white mud with a particle size of ≤0.088mm, and a lignin solution accounting for 3-4% of the total weight of the above raw materials as a binder, wherein Al in the brown corundum particles is 0.1wt%; 2 O 3 ≥95%; Al in mullite particles and fine powder 2 O 3 ≥70%、SiO 2 ≤30%; SiC≥97% in silicon carbide powder, Al in Guangxi white mud fine powder 2 O 3 ≥32%、SiO 2 ≤48%. The highly wear-resistant medium brown corundum, silicon carbide and mullite are all high-purity, highly wear-resistant raw materials. By adding a sintering agent, a dense and firmly combined composite mineral phase is formed at high temperature, which significantly improves the wear resistance and anti-stripping performance of the product. When applied to the kiln mouth of a cement kiln, the service life of the masonry body can be effectively extended.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of refractory materials, in particular to a high wear-resistant brick and a preparation method thereof. Background Art

[0002] High wear-resistant bricks are a kind of refractory products with excellent wear resistance, especially suitable for the parts of cement kiln mouth where cement clinker scouring is more serious. In the past, the refractory bricks commonly used for cement kiln mouth masonry were some traditional products, such as ordinary high-alumina bricks and phosphate-bonded high-alumina bricks. These products have poor wear resistance, low bonding strength, poor scouring resistance, and severe peeling and damage, which shortens the service life and also affects the increase of cement clinker production. High wear-resistant bricks start with the selection of raw materials. First, brown corundum with excellent wear resistance is selected as the main raw material, and sharp-edged mullite is used as the secondary raw material. Silicon carbide fine powder that can improve the crystal structure during the sintering process is introduced, and Guangxi white mud is added as a sintering agent. By adjusting the particle grading and reasonably optimizing the ratio, a strong composite crystal phase is formed through high-temperature sintering, which greatly improves the compressive strength and wear resistance of the product, replacing the traditional products of ordinary high-alumina bricks and phosphate-bonded high-alumina bricks, and the service life is more than doubled. Summary of the invention

[0003] The purpose of the present invention is to provide a high wear-resistant brick for cement kiln mouth and a preparation method thereof, which improves the wear resistance and anti-stripping performance of the product, has a dense structure at high temperature, is firmly bonded, is not easy to be damaged, and has a conventional manufacturing process and is easy to construct.

[0004] To achieve the above purpose, the present invention is implemented through the following technical scheme: a high wear-resistant brick, which is mainly prepared from the following raw materials in mass percentage: 8-12wt% of brown corundum with a particle size of 5-3mm, 20-25wt% of brown corundum with a particle size of 3-1mm, 18-22wt% of brown corundum with a particle size of 1-0mm; 10-15wt% of mullite with a particle size of 3-1mm, 6-10wt% of mullite with a particle size of ≤0.088mm; 15-20wt% of silicon carbide with a particle size of ≤0.088mm; 6-10wt% of Guangxi white mud with a particle size of ≤0.088mm, and lignin solution accounting for 3-4% of the total weight of the above raw materials as a binder.

[0005] Preferably, the brown corundum particles have Al2O3≥95%; the mullite particles and fine powder have Al2O3≥70% and SiO2≤30%; the SiC in silicon carbide powder has SiC≥97%; the Guangxi white mud fine powder has Al2O3≥32% and SiO2≤48%.

[0006] Preferably, the sintering promoting agent is Guangxi white mud, and the binder is lignin solution.

[0007] Preferably, the high wear-resistant brick is mainly made of the following raw materials in mass percentage: 8-12wt% of brown corundum with a particle size of 5-3mm, 20-25wt% of brown corundum with a particle size of 3-1mm, 18-22wt% of brown corundum with a particle size of 1-0mm; 10-15wt% of mullite with a particle size of 3-1mm, 6-10wt% of mullite with a particle size of ≤0.088mm; 15-20wt% of silicon carbide with a particle size of ≤0.088mm; 6-10wt% of Guangxi white mud with a particle size of ≤0.088mm, and lignin solution accounting for 3-4% of the total weight of the above raw materials as a binder. In the high wear-resistant brick, Al2O3≥62%, SiC≥15%, and SiO2≤13%.

[0008] A high wear-resistant brick and a preparation method thereof, comprising the following steps:

[0009] Step 1, raw material pretreatment: first weigh the raw materials and the ingredients with particle size requirements, then screen the weighed main materials, and at the same time, the materials obtained by screening can be matched according to the ratio of brown corundum particles and mullite particles, placed in a mixer for dry mixing for 2-3 minutes, and antioxidants are added inside during dry mixing;

[0010] Step 2: Processing auxiliary materials: Add a binder into the mixed granular material A obtained by dry mixing, place it in a stirring mill and mix and grind for 3-5 minutes;

[0011] Step 3, material collection: After the obtained mixed granular material A is mixed and ground, the mixed granular material A is placed in a mixing tank, and a binder, silicon carbide fine powder, and Guangxi white mud fine powder are added during stirring and mixed and ground for 8-10 minutes to become a semi-dry plastic mud material, and then the material can be discharged;

[0012] Step 4: Weigh the mixed mud material A according to the weight required by the process card and add it into the brick mold to form it. When forming the brick, a 630t electric-controlled screw press is used to form the brick and the demoulding system of the press is used to demould the brick. The demoulded brick is placed on the drying car. The bulk density of the semi-finished product is controlled at 2.95-3.02g / cm 3 ;

[0013] Step 5: Send the drying cart with the bricks into the dryer. After drying at 110-120℃×24h, detect the residual moisture in the bricks to ensure that the residual moisture is ≤0.7%;

[0014] Step 6: The dried bricks are transported by the operator and loaded into the kiln car, pushed into a 110-meter high-temperature tunnel, and then subjected to a high temperature of 1580°C in the kiln. At the same time, it needs to be fired for 10-12 hours to obtain the finished wear-resistant brick body.

[0015] Preferably, in step 1, the fineness of the mixed powder is 180-200 mesh.

[0016] Preferably, the step six also includes the following steps:

[0017] S701. Preparation: The operator needs to place the finished wear-resistant bricks in the cleaning box and clean the finished wear-resistant bricks for 10-60 minutes to ensure that the surface of the bricks is clean, flat and free of grease, dust or other pollutants;

[0018] S702, coating preparation: match the silicon nitride, titanium nitride, silicon carbide and water required for the hard coating in a certain proportion, then transport them into a mixing tank and beat them to form a colloid for large-scale application;

[0019] S703, coating machine for preparation and coating: the operator needs to place the finished wear-resistant brick body in the coating machine, and brush the finished wear-resistant brick body for 10-30 minutes.

[0020] Preferably, the antioxidant is 2,6-di-tert-butyl-p-cresol.

[0021] Preferably, the screening is performed using a 180-mesh molecular sieve, and the material on the sieve is vacuum transported by a pipeline back to the ball mill for further ball milling. The ball milling and screening are all carried out in a closed manner, the material is vacuum transported, the gas and material are separated by air blowing and vibration, and the dust-containing exhaust gas after gas-material separation is filtered through a filter element filter.

[0022] The present invention provides a high wear-resistant brick and a preparation method thereof. The brick has the following beneficial effects:

[0023] The highly wear-resistant medium brown corundum, silicon carbide and mullite of the present invention are all high-purity and highly wear-resistant raw materials. By adding a sintering agent, a dense and firmly combined composite mineral phase is formed at high temperature, which significantly improves the wear resistance and anti-stripping performance of the product. When applied to the kiln mouth of a cement kiln, the service life of the masonry body can be effectively extended. DETAILED DESCRIPTION

[0024] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0025] Embodiment 1:

[0026] The embodiment of the present invention provides a high wear-resistant brick, which is mainly prepared from the following raw materials in percentage by mass: 8-12wt% of brown corundum with a particle size of 5-3mm, 20-25wt% of brown corundum with a particle size of 3-1mm, 18-22wt% of brown corundum with a particle size of 1-0mm; 10-15wt% of mullite with a particle size of 3-1mm, 6-10wt% of mullite with a particle size of ≤0.088mm; 15-20wt% of silicon carbide with a particle size of ≤0.088mm; 6-10wt% of Guangxi white mud with a particle size of ≤0.088mm, and lignin solution accounting for 3-4% of the total weight of the above raw materials as a binder.

[0027] The brown corundum particles contain Al2O3≥95%; the mullite particles and fine powder contain Al2O3≥70% and SiO2≤30%; the SiC in the silicon carbide powder is≥97%; the Guangxi white mud fine powder contains Al2O3≥32% and SiO2≤48%.

[0028] The sintering agent is Guangxi white mud, and the binder is lignin solution.

[0029] The high wear-resistant brick is mainly prepared from the following raw materials in mass percentage: 8-12wt% of brown corundum with a particle size of 5-3mm, 20-25wt% of brown corundum with a particle size of 3-1mm, 18-22wt% of brown corundum with a particle size of 1-0mm; 10-15wt% of mullite with a particle size of 3-1mm, 6-10wt% of mullite with a particle size of ≤0.088mm; 15-20wt% of silicon carbide with a particle size of ≤0.088mm; 6-10wt% of Guangxi white mud with a particle size of ≤0.088mm, and lignin solution accounting for 3-4% of the total weight of the above raw materials as a binder. In the high wear-resistant brick, Al2O3≥62%, SiC≥15%, and SiO2≤13%.

[0030] The above raw materials are mixed and ground by a wet mill, and then formed into blanks by a 630t electric screw press. The blanks are dried at 110-120℃×24h and then loaded into the kiln. After being fired at a high temperature of 1580℃, the finished wear-resistant bricks can be obtained. Its main chemical composition and performance indicators are shown in Table 1.

[0031] Embodiment 2:

[0032] The high wear-resistant bricks for cement kiln mouth of this embodiment are made of 8wt% brown corundum with a particle size of 5-3mm, 25wt% brown corundum with a particle size of 3-1mm, 20wt% brown corundum with a particle size of 1-0mm, 11wt% mullite with a particle size of 3-1mm, 10wt% mullite with a particle size of ≤0.088mm, 16wt% silicon carbide with a particle size of ≤0.088mm, 10wt% Guangxi white mud with a particle size of ≤0.088mm, and lignin solution accounting for 3.5% of the total weight of the above raw materials as a binder. The high wear-resistant bricks contain Al2O3≥62%, SiC≥15%, and SiO2≤13%.

[0033] The above raw materials are mixed and ground by a wet mill, and then formed into blanks by a 630t electric screw press. The blanks are dried at 110-120℃×24h and then loaded into the kiln. After being fired at a high temperature of 1580℃, the finished wear-resistant bricks can be obtained. Its main chemical composition and performance indicators are shown in Table 1.

[0034] Embodiment three:

[0035] The high wear-resistant bricks for cement kiln mouth of this embodiment are made of 9wt% brown corundum with a particle size of 5-3mm, 23wt% brown corundum with a particle size of 3-1mm, 21wt% brown corundum with a particle size of 1-0mm, 12wt% mullite with a particle size of 3-1mm, 9wt% mullite with a particle size of ≤0.088mm, 17wt% silicon carbide with a particle size of ≤0.088mm, 9wt% Guangxi white mud with a particle size of ≤0.088mm, and lignin solution accounting for 3.5% of the total weight of the above raw materials as a binder. In the high wear-resistant bricks, Al2O3≥62%, Si C≥15%, and SiO2≤13%.

[0036] The above raw materials are mixed and ground by a wet mill, and then formed into blanks by a 630t electric screw press. The blanks are dried at 110-120℃×24h and then loaded into the kiln. After being fired at a high temperature of 1580℃, the finished wear-resistant bricks can be obtained. Its main chemical composition and performance indicators are shown in Table 1.

[0037] Embodiment 4:

[0038] The high wear-resistant bricks for cement kiln mouth of this embodiment are made of 11wt% brown corundum with a particle size of 5-3mm, 24wt% brown corundum with a particle size of 3-1mm, 18wt% brown corundum with a particle size of 1-0mm, 14wt% mullite with a particle size of 3-1mm, 7wt% mullite with a particle size of ≤0.088mm, 20wt% silicon carbide with a particle size of ≤0.088mm, 6wt% Guangxi white mud with a particle size of ≤0.088mm, and lignin solution accounting for 3.5% of the total weight of the above raw materials as a binder. In the high wear-resistant bricks, Al2O3≥62%, Si C≥15%, and SiO2≤13%.

[0039] The above raw materials are mixed and ground by a wet mill, and then formed into blanks by a 630t electric screw press. The blanks are dried at 110-120℃×24h and then loaded into the kiln. After being fired at a high temperature of 1580℃, the finished wear-resistant bricks can be obtained. Its main chemical composition and performance indicators are shown in Table 1.

[0040] Scale 1:

[0041] The preparation method of this comparative example is the same as that of Example 1, except that when performing step 1, brown corundum particles are not added to the mixed raw materials.

[0042] Comparative Example 2:

[0043] The preparation method of this comparative example is the same as that of Example 1, except that in step 1, mullite particles are not added when mixing the raw materials.

[0044] Comparative Example 3:

[0045] The preparation method of this comparative example is the same as that of Example 1, except that when performing step 2, no antioxidant is added internally.

[0046] Table 1 Performance index of high wear-resistant bricks in Examples 1 to 4

[0047]

[0048] The relevant technical indicators of Examples 1-4 can meet the requirements of cement kiln mouth. In comparison, the particle gradation of Example 1 is more reasonable, the amount of critical large particles of 5-3 mm is moderate, and the amount of various fine powders added is also optimal. The preferred Example 1 helps to improve the bulk density and compressive strength of the product, and has the best wear resistance and the lowest wear rate under the same experimental conditions.

[0049] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A highly wear-resistant brick, characterized in that: The high wear-resistant brick is mainly prepared from the following raw materials in mass percentage: 8-12wt% of brown corundum particles with a particle size of 5-3mm, 20-25wt% of brown corundum particles with a particle size of 3-1mm, 18-22wt% of brown corundum particles with a particle size of 1-0mm; 10-15wt% of mullite particles with a particle size of 3-1mm, 6-10wt% of mullite fine powder with a particle size of ≤0.088mm; 15-20wt% of silicon carbide fine powder with a particle size of ≤0.088mm; 6-10wt% of Guangxi white mud fine powder with a particle size of ≤0.088mm and lignin solution accounting for 3-4% of the total weight of the above raw materials are used as binders, the brown corundum particles contain Al2O3≥95%; the mullite particles and fine powder contain Al2O3≥70%, SiO2≤30%; the silicon carbide fine powder contains SiC≥97%, the Guangxi white mud fine powder contains Al2O3≥32%, SiO2≤48%, the Guangxi white mud fine powder is a sintering agent, the high wear-resistant brick contains Al2O3≥62%, SiC≥15%, SiO2≤13%; The raw material pretreatment includes: matching the brown corundum particles and the mullite particles in a matching ratio and placing them in a mixer for dry mixing for 2-3 minutes, and adding an antioxidant inside during dry mixing; The antioxidant is 2,6-di-tert-butyl-p-cresol.

2. The method for preparing a highly wear-resistant brick according to claim 1, characterized in that: The following steps are involved: Step 1, raw material pretreatment: firstly, the raw materials and the ingredients with particle size requirements are weighed, then the weighed main materials are screened, and at the same time, they are matched according to the ratio of brown corundum particles and mullite particles and placed in a mixer for dry mixing for 2-3 minutes, and antioxidants are added inside during dry mixing to obtain mixed granular material A; Step 2: Processing auxiliary materials: Add a binder into the mixed granular material A obtained by dry mixing, place it in a stirring mill and mix and grind for 3-5 minutes; Step 3, material collection: After the obtained mixed granular material A is mixed and ground, it is placed in a mixing tank, and silicon carbide fine powder, mullite fine powder and Guangxi white mud fine powder are added during stirring and mixed and ground for 8-10 minutes to form a semi-dry plastic mud material, and then the material can be discharged to obtain mud material A; Step 4: Weigh the mixed mud material A according to the weight required by the process card and add it into the brick mold to pressurize it to form. When forming the brick, a 630t electric-controlled screw press is required to make the brick and the demoulding system of the press is used to demould the brick. The demoulded brick is placed on the drying car. The bulk density of the semi-finished product is controlled at 2.95-3.02g / cm³. Step 5: Send the drying cart with the bricks into the dryer. After drying at 110-120℃×24h, detect the residual moisture in the bricks to ensure that the residual moisture is ≤0.7%; Step 6: The dried bricks are transported by the operator and loaded into the kiln car, pushed into a 110-meter high-temperature tunnel, and then subjected to a high temperature of 1580°C in the kiln. At the same time, it needs to be fired for 10-12 hours to obtain the finished wear-resistant brick body.

3. The method for preparing a highly wear-resistant brick according to claim 2, characterized in that: The screening is performed using a 180-mesh molecular sieve, and the material on the sieve is vacuum transported by a pipeline back to the ball mill for further ball milling. The ball milling and screening are all performed in a closed manner, the material is vacuum transported, the gas and material are separated by air blowing and vibration, and the dust-containing exhaust gas after the gas and material separation is filtered through a filter element filter.

Citation Information

Patent Citations

  • Method for producing silicon mullite abrasive brick

    CN101712551A

  • Mullite corundum carbide silica brick for joint part of transitional zone and firing zone of cement kiln

    CN109534833A